2008
DOI: 10.1097/ta.0b013e31816c5ca6
|View full text |Cite
|
Sign up to set email alerts
|

Gut Ischemia/Reperfusion Induced Acute Lung Injury is an Alveolar Macrophage Dependent Event

Abstract: ALI values are expressed as EBD lung leakage (microg EBD/g dry lung weight). EBD lung leakage values in the CLOD-LIP group were 32.59 +/- 12.74 for I/R, 27.74 +/- 7.99 for LAP, and 33.52 +/- 10.17 for CTR. In the LIP group, lung leakage values were 58.02 +/- 18.04 for I/R, 31.90 +/- 8.72 for LAP, and 27.17 +/- 11.48 for CTR. In the UNTREAT group, lung leakage values were 55.60 +/- 10.96 for I/R, 35.99 +/- 6.89 for LAP, and 30.83 +/- 8.41 for CTR. Within each group, LAP values did not differ from CTR values. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 29 publications
1
25
0
5
Order By: Relevance
“…In the present study, protein levels in BAL were significantly increased after blunt chest trauma. Comparable to our own previous experiments on Evans blue lung-plasma ratio (26), these data indicate that lung contusion induces a breakdown of the alveolocapillary barrier as described previously (6,27). Under this condition, the transfer of mediators from the lung to the bloodstream and vice versa is facilitated and chemokines may arrive in the circulation to stimulate immune cells.…”
Section: Discussionsupporting
confidence: 84%
“…In the present study, protein levels in BAL were significantly increased after blunt chest trauma. Comparable to our own previous experiments on Evans blue lung-plasma ratio (26), these data indicate that lung contusion induces a breakdown of the alveolocapillary barrier as described previously (6,27). Under this condition, the transfer of mediators from the lung to the bloodstream and vice versa is facilitated and chemokines may arrive in the circulation to stimulate immune cells.…”
Section: Discussionsupporting
confidence: 84%
“…I/R causes gut barrier disruption and endotoxin entry into the circulation, leading to severe systemic inflammation and eventually multiple organ failure [4-7]. Acute lung injury (ALI) is a common complication that occurs after intestinal I/R and is a major contributor to the high mortality rate [7-11]. Limited pharmacological treatment options exist for ALI, with most targeting inflammatory mediators and oxidative stress pathways [12].…”
Section: Introductionmentioning
confidence: 99%
“…After activation by proinflammatory cytokines and chemotactic factors, neutrophils are then able to penetrate the vasculature and transmigrate through the interstitium into the alveolar space [18,19]. In addition, alveolar macrophages are also essential players in the initiation of ALI [11,20]. …”
Section: Introductionmentioning
confidence: 99%
“…Kubes et al 28 showed that most of the liver I/R models (including liver transplantation) have some degree of intestinal ischemia, which enhances the liver injury by inducing the release of toxins and intestinal neutrophil recruitment 27,29 . Recently, intestinal transplantation has become the preferred therapy for patients with short bowel syndrome, with intolerance to total parenteral nutrition 14,17,19 .…”
mentioning
confidence: 99%